Intersectionality contesting privilege; fostering inclusion. - Hassen, Ferhan Mohammed; Göktürk, Şöheyda; Tülübaş, Tijen (Social Identities, 2023)
Identity categories have the potential to become salient factors for unequal treatment within a public school setting in Ethiopia. Public school teachers can experience administrative procedures and processes differently based on the identity categories they belong. Hence, this situation can become a condition for the problem of horizontal inequality within public schools with teachers of diverse social identities. Horizontal inequality was investigated at the state level using unitary identity category difference. However, horizontal inequality within school diversity using an intersectional perspective is ignored, particularly in the Ethiopian public school context. Accordingly, this study investigated horizontal inequality within school diversity using an intersectionality lens. We investigated out-group member teachers' horizontal inequality experience within a public school setting through ideas conceived of equal treatment for public school teachers. Using qualitative hermeneutic phenomenology design the data were collected from 10 former teachers sampled with both snowball and maximum variation techniques. Content analysis of the data not only revealed that the intersection of ethnic, race, religion and political affiliation identity categories determine teachers' access to privileged space within public school diversity but also the manner of horizontal inequality establishment and othering instruments. Horizontal inequality within public schools' diversity may be eliminated by first admitting it exists and then taking additional measures to ensure equality policies and legislation are implemented to serve their intended purposes.